ChemInform Abstract: Enantioselective Biomimetic Total Syntheses of Kuwanons I (Ia) and J (Ib) and Brosimones A (II) and B (III). Issue 8 (February 2015) - Han, Jianguang; Li, Xia; Guan, Yong; Zhao, Wenjun; Wulff, William D.; Lei, Xiaoguang
Abstract The synthesis of the title compounds is accomplished from a common intermediate.